2020
DOI: 10.1039/d0cs00259c
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress: an arising target for metal-based anticancer agents

Abstract: Metal anticancer agents are rapidly emerging as selective, potent therapeutics that exhibit anticancer activity by inducing endoplasmic reticulum stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(118 citation statements)
references
References 191 publications
2
115
0
1
Order By: Relevance
“…Ca 2+ overload also plays an important role in the occurrence of drug-induced ERS (Cheng et al, 2018). Drugs initiate the Ca 2+ channels on the tumor cell membrane after entering the cell through the transporters, which causes the influx of extracellular Ca 2+ (King and Wilson, 2020). Ca 2+ is released from the ER when the Ca 2+ concentration in the cytoplasm reaches a certain level (Cai et al, 2016), which can lead to Ca 2+ overload (Nyberg and Espinosa, 2016).…”
Section: Drug-induced Ers In Solid Tumorsmentioning
confidence: 99%
“…Ca 2+ overload also plays an important role in the occurrence of drug-induced ERS (Cheng et al, 2018). Drugs initiate the Ca 2+ channels on the tumor cell membrane after entering the cell through the transporters, which causes the influx of extracellular Ca 2+ (King and Wilson, 2020). Ca 2+ is released from the ER when the Ca 2+ concentration in the cytoplasm reaches a certain level (Cai et al, 2016), which can lead to Ca 2+ overload (Nyberg and Espinosa, 2016).…”
Section: Drug-induced Ers In Solid Tumorsmentioning
confidence: 99%
“…Capitalizing on these advantages, a variety of metal-containing compounds have already been clinically approved for a wide range of therapeutic applications. Increasing efforts to not only identify bioactive metal complexes [41] but deeply understand their mechanism of action [87][88][89][90] will be an important next step in their advancement and greater acceptance in the medical community (see Outstanding questions). Further investigation into the therapeutic applications of metal complexes will yield novel compounds with increased potency and selectivity and may even lead to the discovery of entirely new therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The Pearson's correlation coefficient of Ir-cR8 with different markers showed that, although diffused in the cell, Ir-cR8 preferred to distribute in the endoplasmic reticulum and the mitochondria rather than in the lysosomes, a localisation potentially having correlation with the oncosis-like cell death. 55 Next, the intracellular molecular mechanisms that may be associated with this mode of death were investigated. As the signalling pathways that regulate oncosis have not been fully elucidated, circumstantial evidence was searched to verify whether the cell death caused by the Ir-peptides was of oncotic nature.…”
Section: Resultsmentioning
confidence: 99%